2000
DOI: 10.2134/jeq2000.00472425002900020019x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Procedures for Characterizing Manure Phosphorus

Abstract: Phosphorus runoff from agricultural land contributes to accelerated eutrophication of surface waters. In areas with intensive animal farming, P loss from manured fields may be elevated due to high concentrations of soluble P in manure. We characterized P in dairy and poultry manure for the relative dissolution and fraction distribution using deionized water (H2O), 0.5 M NaHCO3, 0.1 M NaOH, 1.0 M HCl, and 5% trichloroacetic acid (TCA). Two extraction procedures were tested: (i) independent, with dried, ground s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
178
5
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(218 citation statements)
references
References 0 publications
22
178
5
7
Order By: Relevance
“…However, this is likely to influence phosphorus solubility. For example, Sharpley and Moyer (17) reported that most of the phosphate in a range of fresh manures stored at 4 °C was recovered in the NaOH fraction, whereas Dou and colleagues (18) recovered most of the phosphate from a dairy manure dried at 65 °C in the initial water extract, although this was performed exhaustively. Leinweber and colleagues (16) freeze-dried a liquid swine manure and a chicken manure prior to sequential fractionation but recovered only 60% of the phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely to influence phosphorus solubility. For example, Sharpley and Moyer (17) reported that most of the phosphate in a range of fresh manures stored at 4 °C was recovered in the NaOH fraction, whereas Dou and colleagues (18) recovered most of the phosphate from a dairy manure dried at 65 °C in the initial water extract, although this was performed exhaustively. Leinweber and colleagues (16) freeze-dried a liquid swine manure and a chicken manure prior to sequential fractionation but recovered only 60% of the phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Dou et al (2000) found that approximately 70 % of the P in cattle manure was water-extractable, but this type of information is not available for the FYM used in the semi-arid region of Brazil. There is no information either on the transformations of this P source after several years of FYM application to the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) is not only an important 4 plant nutrient, but also a major contaminant in the water environment. However, information on the 5 accumulation and distribution of P in organic vegetable soils under plastic greenhouse conditions is 6 limited, relative to the open cultivation systems. Therefore, twenty-six plastic greenhouse vegetable PGVS with similar soil and cultivation practices were selected.…”
mentioning
confidence: 99%